PET/CT imaging of esophageal cancer targeting tumor cell specific αvβ6-integrin expression - Bendová, Kateřina Dvořáková; Groll, Tanja; Neužilová, Barbora; Krasulová, Kristýna; Nový, Zbyněk; Reissig, Falco; Steiger, Katja; Boxberg, Melanie; Eppard, Elisabeth; Wuestemann, Jan; Hajdúch, Marián; Jesinghaus, Moritz; et al. (European journal of nuclear medicine and molecular imaging, 2025)
PURPOSE: To assess the potential of αvβ6-integrin as a theranostic target in esophageal cancer. METHODS: Membranous β6-integrin (ITGB6) expression was analyzed in 306 specimens of human esophageal squamous cell carcinoma (ESCC) obtained by immunohistochemistry (IHC) from 100 patient cases (1, 37, 58, and 4 of grade G1, G2, G3, and G4, respectively). Ga-68 labeling of D0103 was done manually for preclinical experiments and fully automated for clinical application. Preclinical characterization of Ga-68-D0103 was performed in SCID mice bearing subcutaneous xenografts of H2009 (αvβ6-positive) or MDA-MB-231 (αvβ6-negative) carcinoma cell lines, by ex vivo biodistribution (10, 30, 90, and 180 min p.i) and PET imaging (30, 90, and 180 min p.i.)., without and with co-injection of gelofusine (4% succinylated gelatin). A patient with type-II diabetes (f, 68y, 115 kg) with proximal G2 ESCC was investigated by Ga-68-D0103 PET/CT (193 MBq) at 15, 45, 90, and 104 min p.i.. RESULTS: 99% of ESCC cases were found β6-integrin positive by IHC, of which 48%, 31%, and 20% showed strong, moderate, and low ITGB6 expression, respectively, with no correlation to tumor grade. Ex vivo biodistribution of Ga-68-D0103 in H2009 xenografted mice after 30, 90, and 180 min showed tumor-to-blood ratios of 6.8, 37, and 124, respectively; tumor-to-muscle ratios of 12, 14, and 36, respectively; tumor-to-liver ratios of 10, 17, and 14, respectively; and tumor-to-pancreas ratios of 20, 47, and 56, respectively. Co-administration of gelofusine did not change the tumor uptake but reduced the kidney uptake by 89% (from 178%iA/g to 19.1%iA/g, 90 min p.i.), resulting in an 8.7-fold higher tumor/kidney ratio. µPET imaging in H2009 xenografted mice confirmed a high tumor uptake and low background already 30 min p.i.. Blockade biodistribution and µPET in αvβ6-(-) MDA-MB-231 mice demonstrated target specificity. Clinical PET/CT of a patient with ESCC showed increasing tracer uptake over time in the primary tumor (SUVmax 9.0 and 11.3 at 15 and 104 min p.i., respectively) and in a lymph node metastasis (SUVmax 19.5 and 28.3, respectively), and a decreasing blood pool activity (SUVmean 2.75 and 0.98, respectively). CONCLUSIONS: High (99%) membranous expression frequency and density on tumor cells underscores the potential of αvβ6-integrin as a theranostic target in ESCC, suggesting that αvβ6-integrin PET/CT imaging may adopt a role in re-staging and therapy guidance in this cancer type. The prolonged tumor retention furthermore indicates a therapeutic potential of αvβ6-integrin targeted radiopharmaceuticals when labeled with radionuclides such as lutetium-177, terbium-161, or actinium-225.
Keywords: Positron Emission Tomography; Surveillance; Esophageal Cancer; Theranostics; Integrins